"Fisiolab" physiological signals acquisition system. - Martinez Ortiz, A.; García González, Ma. T.; Peña Castillo, M.; Santos Cortez, A. (Revista Mexicana de Ingenieria Biomedica, 2018)
It presents a system of acquisition of physiological signals by means of amplifiers, analog / digital converter, printer, graph and a personal computer that uses a program of registration and storage of information in a database, becoming an acquisition unit, record and storage of physiological signals called "Fisiolab".